Drying characteristics and quality evaluation in convective drying of Cissus quadrangularis Linn. - Setthawat Thanimkarn; Ekkapong Cheevitsopon; Jiraporn Sripinyowanich Jongyingcharoen (My University, 2018)
This study aimed to investigate the effect of drying temperature (40, 60, 80, and 100°C) on drying characteristics of Cissus quadrangularis Linn. (CQ) undergoing convective drying. Physical properties and phytochemicals of the dried CQ were also evaluated. CQ with the thickness of 5 mm was dried from about 10 to 0.1 g water/g dry matter. The results showed that increasing drying temperature increased drying rate (DR) and effective moisture diffusivity (D eff ) and consequently decreased drying time. The drying time, maximum DR, and Deff were in the ranges of 85-1920 min, 0.0059-0.0248 g water/g dry matter·min, and 0.7302-9.1281×10 -9 m 2 /s, respectively. Lower drying temperature could preserve quality of the dried CQ. Decreasing drying temperature resulted in greener and lower bulk density and shrinkage. The greatest total phenolic content (TPC) and quercetin content were obtained by drying the CQ at 60°C.
Keywords: Shrinkage; Food Quality and Safety Studies